2022
DOI: 10.26464/epp2022019
|View full text |Cite
|
Sign up to set email alerts
|

Reply to Comment by Lamy et al. on “Locating the source field lines of Jovian decametric radio emissions”

Abstract: Locating the source of decametric (DAM) radio emissions is a key step in the use of remote radio observations to understand the Jovian magnetospheric dynamics and their interaction with the planet's moons. Wang YM et al. (2020) presented a method by which recorded arc-shaped DAM emissions in the radio dynamic spectra can be used to locate the source of a DAM. An Io-related DAM event on March 14, 2014 was used to demonstrate the method. A key parameter in the method is whether the DAM is emitted in the norther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
5
1
0
Order By: Relevance
“…Unfortunately, the authors applied it to a single Io‐DAM event observed by Wind and STEREO A/B waves instruments, erroneously identified as an Io‐B emission instead of an Io‐D one (Lamy et al., 2022). The correction of the hemisphere of origin in turn yields larger θ ( f ) ∼ 72 − 65° and lower E e − ∼ 5 − 9 keV (Wang et al., 2022), in excellent agreement with our results summarized in Figure 11. The correction brought by Wang et al.…”
Section: Single‐point Radio Observations: Toward a Statistical Studysupporting
confidence: 92%
See 1 more Smart Citation
“…Unfortunately, the authors applied it to a single Io‐DAM event observed by Wind and STEREO A/B waves instruments, erroneously identified as an Io‐B emission instead of an Io‐D one (Lamy et al., 2022). The correction of the hemisphere of origin in turn yields larger θ ( f ) ∼ 72 − 65° and lower E e − ∼ 5 − 9 keV (Wang et al., 2022), in excellent agreement with our results summarized in Figure 11. The correction brought by Wang et al.…”
Section: Single‐point Radio Observations: Toward a Statistical Studysupporting
confidence: 92%
“…The correction brought by Wang et al. (2022) also illustrated that a misidentification of the Io‐DAM hemisphere yielded in their case a systematic error up to −7° on θ and +9 keV on E e − .…”
Section: Single‐point Radio Observations: Toward a Statistical Studymentioning
confidence: 90%
“…The correction of the hemisphere of origin in turn yields larger θ(f ) ∼ 72 − 65 • and lower E e− ∼ 5 − 9 keV (Wang et al, 2022), in excellent agreement with our results summarized in Figure 11. The correction brought by (Wang et al, 2022) also illustrated that a misidentification of the Io-DAM hemisphere yielded in their case a systematic error up to −7 • on θ and +9 keV on E e− . Martos et al (2020) developed a different method, applied to one example of Io-A, B, C and D events (sometimes made of multiple arcs) as observed by Juno/Waves alone.…”
Section: Application To Case Studies Investigated In Other Recent Art...supporting
confidence: 91%
“…Unfortunately, the authors applied it to a single of Io-DAM event observed by Wind and STEREO A/B waves instruments, erroneously identified as an Io-B emission instead of an Io-D one (Lamy et al, 2022). The correction of the hemisphere of origin in turn yields larger θ(f ) ∼ 72 − 65 • and lower E e− ∼ 5 − 9 keV (Wang et al, 2022), in excellent agreement with our results summarized in Figure 11. The correction brought by (Wang et al, 2022) also illustrated that a misidentification of the Io-DAM hemisphere yielded in their case a systematic error up to −7 • on θ and +9 keV on E e− .…”
Section: Application To Case Studies Investigated In Other Recent Art...supporting
confidence: 83%
“…Unfortunately, the authors applied it to a single Io-DAM event observed by Wind and STEREO A/B waves instruments, erroneously identified as an Io-B emission instead of an Io-D one (Lamy et al, 2022). The correction of the hemisphere of origin in turn yields larger θ(f) ∼ 72 − 65° and lower E e− ∼ 5 − 9 keV (Wang et al, 2022), in excellent agreement with our results summarized in Figure 11. The correction brought by Wang et al (2022) also illustrated that a misidentification of the Io-DAM hemisphere yielded in their case a systematic error up to −7° on θ and +9 keV on E e− .…”
Section: Application To Case Studies Investigated In Other Recent Art...supporting
confidence: 82%